BENTUK SENI DALAM UPACARA UMAT HINDU DI KALIMANTAN TENGAH - Anak Agung Gede Wiranata; Nyoman Sarma; Ni Made Ratini (Fakultas Dharma Duta dan Brahma Widya, 2025)
Art in the Hindu perspective holds a fundamental position and is inseparable from religious rituals. Artistic works are a form of devotion and a longing to connect with the very source of art itself, while also fulfilling human needs in daily life. Hindu art is derived from the sacred Vedic scriptures, with specific art forms (such as expression, song, drama, and sentiment) originating from different Vedas. Artistic creativity is synonymous with religion, particularly in Hindu communities in Bali, where various art forms (dance, music, visual arts, voice) support the execution of rituals. Sacred art, which functions as an accompaniment to ceremonies, is created through a process involving religious initiation and sacralization, thus being believed to possess magico-religious power. The relationship between art and religion is so intimate that it becomes difficult to distinguish between religious practice and artistic performance. Art is also viewed as a symbol of Satyam (Truth), Siwam (Purity), and Sundharam (Beauty), and serves as a medium to facilitate the expression of devotion to God. Through the concept of Ngayah (selfless service), art is offered sincerely as a form of dedication. The preservation of sacred art, especially among the younger generation, is crucial for maintaining its continuity as part of Hindu identity and spirituality.